(untitled) (Journal of Surgical Sciences, 2026)
Introduction: Gastric cancer is one of the most common malignant tumors. Early detection of gastric cancer is important for curative treatment and better survival rate. The aim of this present study is to compare between preoperative Endoluminal Ultrasound (EUS), Ultrasonogram (USG), CT Scan findings with peroperative findings and/or postoperative histopathological findings & evaluate the usefulness of EUS, USG & CT scan for determining resectability of carcinoma stomach. Methods: This cross-sectional descriptive study conducted at Dhaka Medical College & Hospital from March 2016 to August 2017. A total 38 patients were selected based on inclusion and exclusion criteria. Then they were staged by CT scan of abdomen, USG of whole abdomen and EUS. Finally, all those underwent laparotomy & histopathological assessment were done for determining resectibility. Results: Regarding T staging, 25 (78.10%),22 (68.70%) & 28 (75%) out of 38 patients were staged correctly with EUS, CT & USG respectively. Regarding N staging, 24 (75%),22 (68.8%) & 25 (65.7%) out of 38 patients were staged correctly with EUS, CT scan & USG respectively. The overall accuracy of EUS, CT scan & USG for determination of the T stage was 78.1%, 68.7 % & 75% respectively & N stage was 75 %, 68.8 % & 65.6%. In EUS staging 28 cases were found resectable preoperatively but during operation 26 cases were found resectable and 2 cases were found un-resectable. Among rest of the preoperative un-resectable 10 cases, we found 6 cases were resectable and 4 cases were actually un-resectable. So, the accuracy, sensitivity, specificity of EUS for resectibility was 92.9%, 81.2% and 66.7% respectively. In CT staging 31 cases were found resectable preoperatively but during operation 27 cases were found resectable and 4 cases were found un-resectable. Among rest of the preoperative un-resectable 7 cases, we found 5 cases were resectable and 2 cases were actually un-resectable. So, the accuracy, sensitivity, specificity of CT for resectibility was 87.1%, 84.4% and 33.3% respectively. In USG staging 29 cases were found resectable preoperatively but during operation 24 cases were found resectable and 5 cases were found un-resectable. Among rest of the preoperative un-resectable 9 cases, we found 8 cases were resectable and 1 case was actually un-resectable. So, the accuracy, sensitivity, specificity of USG for resectibility was 82.7%, 75% and 17% respectively. Conclusion: The accurate preoperative staging is extremely essential for proper decision making and stage dependent management, which improve 5 years survival rates or limits unnecessary laparotomy in advanced stage. Journal of Surgical Sciences 2023;27(2): 46-52